Characterization of washing aggregate sludge waste as a novel supplementary cementitious material: Experimental study and life cycle assessment - Miyan, Nausad; Omur, Tarik; Bilici, Senem; Ozkan, Hakan; Kabay, Nihat (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2024)
Washing aggregate sludge (WAS), a waste collected from aggregate quarries, is examined for its application as a partial substitute of ordinary portland cement (OPC). The raw WAS initially dried, ground, and then subjected to 700 degrees C and 900 degrees C. In this study, various paste and mortar mixtures were produced to investigate the pozzolanic property and environmental impacts of raw WAS and treated WAS at a selected temperature of 700 degrees C. The pozzolanic activity of both raw and treated WAS at 700 degrees C was verified using several tests, including X-ray diffraction (XRD), Frattini test, strength-based evaluation, and thermal analysis. The calcium-silicate-hydrate (C-S-H), portlandite (Ca(OH)2), calcium silicates (C2S and C3S), and calcite (CaCO3) were identified as major reaction products indicating the participation of raw or treated WAS. While the reduced [CaO] concentration and location below the solubility curve confirmed the pozzolanic activity of both powders, the compressive strengths of blended mortars were also found greater than 75% compared to the reference mortar at all testing ages. Treated WAS demonstrated higher pozzolanic activity than raw WAS due to the reduced formation of Ca(OH)2 revealed by thermal and kinetic analysis at different time periods. Life cycle assessment resulted in the reduced CO2 emissions by the blended mortars containing either raw or treated WAS, which suggest their promising mechanical and environmental benefits.
Keywords: Washing aggregate sludge; Pozzolanic activity; Strength activity index; Thermogravimetric analysis; Kinetic analysis; Life cycle assessment; SEWAGE-SLUDGE; PART I; CONCRETE; SLAG; ASH; CALCINATION; REACTIVITY; Environmental Sciences & Ecology